IMPLEMENTATION AUGMENTED REALITY INLA GYMNASTICS BASE ON MOBILE - Axel Arya Maitri Cundana; Yonky Pernando (Smart Education, 2022)
Augmented Reality INLA ((International Nature Loving Association ) ) gymnastics is an application to help people watch performances and performances without having to attend directly to the place of activity. This application is made based on mobile, because it is the most widely used by the general public. This application will display the song gymnastics World One Family with a duration of 3 minutes 28 seconds and the actor as an instructor for the gymnastics movement World One Family. The focus of this research is on the INLA team at the Maitreyawira Elementary School in Batam. So that the process of introducing culture through INLA at Maitreyawira Elementary School Batam becomes more practical and interesting. INLA Gymnastics activities at Maitreyawira Elementary School Batam can be carried out again during the Covid-19 pandemic. Increase interest in INLA culture at Maitreyawira Elementary goe in using the Augmented Reality application.